Pengaruh Budaya Organisasi dan Karakteristik Individu Terhadap Motivasi Kerja dan Dampaknya Terhadap Kinerja Pegawai pada Kantor Pertanahan Kabupaten Batanghari - Hupron Faqih Said; Fakhrul Rozi Yamali; Evi Adriani; Fakhrul Rozi Yamali (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to obtain an overview of organizational culture, individual characteristics, and work motivation, as well as employee performance at the Batanghari District Land Office; and to determine the direct and indirect influence of organizational culture and individual characteristics on work motivation and employee performance; as well as to determine the effect of motivation on employee performance. To answer the research objectives, the authors need theoretical studies related to research variables, namely organizational culture theory, individual characteristics, and work motivation, as well as employee performance. In addition, the authors also look for relevant previous research in the form of previous articles/journals and theses to support this research. The population in this study were employees of the Batanghari Regency Land Office, totaling 53 employees. The sampling technique in this study used Saturated Sampling, so that the number of samples in this study amounted to 53 employees. To answer all hypotheses, the analysis technique used is through path analysis. The results of the study show that organizational culture and individual characteristics have an influence on employee motivation and performance, both directly and indirectly. Where based on the results of the t test (partial) and the F test (Simultaneous) show that organizational culture and individual characteristics have a significant and positive influence on motivation and performance, as well as motivation also has a significant and positive influence on performance. This explains that if the organizational culture and individual characteristics can be implemented properly, it will have a positive influence in increasing work motivation which has implications for improving the performance of employees of the Batanghari District Land Office. Based on the results of the study, namely organizational culture, individual characteristics, and work motivation, as well as the performance of the Batanghari Regency Land Office employees in good and quite good condition; organizational culture and individual characteristics have a positive and significant impact on work motivation both directly and indirectly; organizational culture and individual characteristics have a positive and significant impact on employee performance both directly and indirectly; work motivation affects employee performance; and organizational culture and individual characteristics together through motivation can have a direct and indirect effect on the performance of employees of the Batanghari District Land Office.